THE EFFECT OF FREE CASH FLOW AND LEVERAGE ON PROFIT MANAGEMENT WITH FINANCIAL PERFORMANCE AS A MODERATING - Selfiani Selfiani; Yudhistira Adwimurti (Jurnal Ilmiah Manajemen Ubhara, 2023)
In 2017 the case occurred in the company SNP Finance. Five directors and managers of PT Sunprima Nusantara Financing (SNP Finance) were arrested by the authorities related to cases of alleged criminal acts of document forgery, embezzlement, fraud, and money laundering in their business activities as a multifinance company.  SNP Finance is part of Columbia, a retail chain that offers household purchases on credit or installments. In its activities, it is the SNP that supports the purchase of goods made by Columbia with funding sources from banks or debt securities (www.cnnindonesia.com)Research problems: Does free cash flow affect profit management, does leverage affect profit management, does financial performance moderate the relationship between  free cash flow and profit   management, does financial performance moderate the relationship between profit management and profit management.   Purpose of the study: to test free cash flow against profit management, leverage against profit management, financial performance moderating the relationship between leverage and profit management Research method:  secondary quantitative data, with textile companies  as a sample of 36 companies, this study used chow  test, housman test   ,  classical assumption test, autocorrelation test, heteroskecity test, descriptive test, The results of this study state that free cash flow has a positive effect on profit management, leverage has a positive effect   on  profit  management  ,  financial performance strengthens the relationship between  free cash flow  and profit management,  financial performance strengthens   the relationship between leverage and    profit management. Keywords: free cash flow, leverage, Profit management,  financial performance.